Informe y Exploración de Yacimientos de Hierro Zona Sur: El Kaisser, Rezagos, Vegas Peladas, Vegas Atravesadas, Corrales de Pacheco, El Peto, Piedra Imán, Las Tordillas, Monteagudo. Provincia de Mendoza - Peña, Albany F. (1956)
Fil: Peña, Albany F. Ministerio de Industria de la Nación. Dirección Nacional de Minería. Delegación Mendoza; Argentina.